Social media and nonprofits: 8 principles for success - Kanter, Beth (Henry Stewart Talks, 2009)
The conversation, Don't start with the tools, Social media supports your internet strategy, Listening to supporters in their natural environment, Build relationships with influencers, Use metrics to discover what works and what doesn't, Engagement, Cost and value